Optimalisasi Branding UMKM Rempeyek “Mak Sri” Melalui Pengembangan Desain Kemasan Produk dan Pemanfaatan Digital Marketing - Wahyu Ridho; Shabirina Laila Azka (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
In the era of the Industrial Revolution 4.0, many transformations in various life sectors encourage the community to adopt, including MSME actors. In implementing community service activities in Rejoso Village, Nganjuk Regency, KKNTt-MBKM, students found that MSMEs needed help adapting. The MSMEs experienced obstacles in optimizing product potential and developing marketing methods caused by age and the need for understanding in using technology. Therefore, implementing this community service activity aims to help MSMEs build their business by preparing an activity plan to overcome obstacles that include branding and digital marketing assistance activities. The method used is Planning of Action (POA) through the preparation of stages in implementing branding and digital marketing. These stages are conducting surveys, analyzing the potential and constraints on MSME actors, planning the implementation of branding and digital marketing, signing and handing over MoUs, then carrying out branding activities through mentoring the creation of logos, labels, taglines, and banners of MSME products and digital marketing through mentoring the creation and use of Instagram social media accounts and Shopee e-commerce. The results showed that MSMEs experienced the development of products and marketing methods through activities carried out by KKN students.